2006
DOI: 10.1093/jb/mvj008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the mTOR-Raptor Signaling Pathway by the Inhibitor of Heat Shock Protein 90 Geldanamycin

Abstract: Heat shock protein 90 (Hsp90) was co-immunoprecipitated with raptor, the binding partner of the mammalian target of rapamycin (mTOR) from HEK293 cells. Hsp90 was detected in the anti-raptor antibody immunoprecipitates prepared from the cell extract by immunoblot analysis using the anti-Hsp90 antibody, and the association of these two proteins was confirmed by immunoprecipitation from the cells co-expressing Hsp90 and raptor as epitope-tagged molecules. Geldanamycin, a potent inhibitor of Hsp90, disrupted the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
8
39
0
Order By: Relevance
“…Whereas the interaction between Tel2 and Tti1, Tti2, and Reptin was not affected, the binding of ATM, mTOR, ATR, and DNA-PKcs was diminished by Hsp90 inhibition. Consistent with this finding, our previous data indicated that prolonged (16-24 h) treatment with 17-AAG substantially diminished the levels of ATM and DNA-PKcs and had a minor effect on mTOR (Takai et al 2007), and an inhibitory effect of geldanamycin on mTOR activation has been reported (Ohji et al 2006).…”
Section: Inhibition Of Hsp90 Affects Binding Of Tel2 To Atm Atr Mtosupporting
confidence: 83%
“…Whereas the interaction between Tel2 and Tti1, Tti2, and Reptin was not affected, the binding of ATM, mTOR, ATR, and DNA-PKcs was diminished by Hsp90 inhibition. Consistent with this finding, our previous data indicated that prolonged (16-24 h) treatment with 17-AAG substantially diminished the levels of ATM and DNA-PKcs and had a minor effect on mTOR (Takai et al 2007), and an inhibitory effect of geldanamycin on mTOR activation has been reported (Ohji et al 2006).…”
Section: Inhibition Of Hsp90 Affects Binding Of Tel2 To Atm Atr Mtosupporting
confidence: 83%
“…However, there was no detectable loss (degradation) of any of the MRN components nor did 17DMAG disrupt the complex. Ohji et al (46) reported that raptor is an Hsp90 client, and although inhibition of Hsp90 does not result in raptor degradation, it does suppress raptor-mammalian target of rapamycin signaling. Similarly, the activity of the MRN complex may require a stabilizing interaction with Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 binds to raptor in mammalian cells and positively regulates S6K activity. Geldanamycin, an Hsp90 inhibitor in clinical trials for cancer treatment, suppressed binding of raptor to Hsp90 and reduced S6K phosphorylation (Ohji et al, 2006). Some years ago, the Blenis group found that heat shock unexpectedly increased phosphorylation of S6K1 in fibroblasts (Jurivich et al, 1991), a finding also made by another group (Lin et al, 1997).…”
Section: Heat Shockmentioning
confidence: 95%